PENERAPAN MANAJEMEN BUDIDAYA IKAN NILA YANG BAIK DIKELOMPOK PEMBUDIDAYA IKAN GEMARI JAYA KABUPATEN MALANG - Hany Handajani; Ganjar Adhywirawan Sutarjo (Jurnal Abdi Insani, 2022)
The group of fish cultivators who continue to strive to develop intensive freshwater fish farming activities in the Jedong Village, Malang Regency, is the Gemari Jaya fish cultivator group. This fish farming business is relatively new, which was formed in 2019 so it requires assistance from various parties including universities. In running their business, program partners face several problems, namely the lack of proper management of fish farming so that costs and production capacity are not measurable. The purpose of this program is to improve the skills and knowledge of partners regarding the implementation of good Tilapia aquaculture management, the application of water quality management, and the application of fish health management. The method used in this activity is a method of training and mentoring related to the importance of improving good management of tilapia aquaculture, water quality management, and fish health management. The results of the activities obtained are that partners are able to apply management of Tilapia fish farming intensively guided by good fish farming practices (CBIB), Application of water quality management techniques through periodic water quality monitoring, and application of herbal plant-based fish health management at partner locations so that production capacity previously 40% increased to 60%, the target production time from the previous 6 months can be achieved within 5 months. The conclusion of this activity is that the production capacity and time of tilapia cultivation can be measured properly, so that the partner's economy increases.